Influence of the educational model by objectives on the academic performance of the students of the National University of Engineering - Vilchez Vilchez, Tito Roberto (2011)
This article intends to present an overview of the academic reality of higher education at the National University of Engineering and the influence of current educational model in the academic performance of students. Education is one of the most important tools with which you can have a country to ensure their human and social development, so from the university must have a sincere commitment to create an educational revolution to transform, organize and articulate the system all levels in order to ensure quality education to produce an excellent learning the new generation of students, which meets the expectations of this generation to face the challenges of the contemporary world of work. In this millennium has been evidenced in the National Engineering University (UNI) poor academic performance of students, where approximately EL40% of students have a cumulative GPA of less than ten (10) in the vigesimal scale. This fact is striking, considering that at this prestigious university entrants the best students, according to data provided by the Central Registry Office and Statistics UNI, considering that when applying for this university, on average, 8000 applicants, admitted only 800 (10%), but in college, their grade point averages, bordering generally 11 to 12 which is considered a low average in their studies at the university, at the end of it difficult for them to enter the market and abroad. Moreover, in other private universities have footnote 13 as minimum passing grade, allowing them to finish with an average grade top and easily inserted in the international market. This poor performance in UNI explained among other reasons, traditional methods that are implemented in the teaching-learning process supported by objectives, as in most public universities, but have not made the necessary efforts to change this situation; less research has been done to realize the magnitude of the problem. Therefore it is important to note, that the educational activity is not based solely on the issue of rules modifying the rating system or changes in the curriculum and the curriculum, but transcendentally in improving teaching techniques and guiding action, fundamental responsibility of teachers, who require specialized training and, there being a harsh reality in the university system, in which the National Assembly of Rectors (ANR) and the university authorities still do not give the great importance of plain meaning of improving academic quality with adequate monitoring directly related to the university accreditation linked to the profound actions to perform on the road to academic excellence.